2009
DOI: 10.1890/07-1533.1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants

Abstract: Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 28 publications
(33 reference statements)
2
56
0
Order By: Relevance
“…Optimal defense theory can also help to explain this pattern, one most herbivores in regions with high temperature (e.g. Neotropical savanna) tend to be strictly nocturnal (Fagundes et al 1996;Strauss et al 2009;Byk & Del-Claro 2010). Moreover, due to the plants reduce greatly the nectar secretion when this resource is removed in low frequency (Koptur 1983;Pyke 1991;Heil et al 2000), the ants' visitation on EFN of A. verrucosa may also have night foraging in arid and semi-arid regions (Briese & Macauley 1980;Oliveira et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal defense theory can also help to explain this pattern, one most herbivores in regions with high temperature (e.g. Neotropical savanna) tend to be strictly nocturnal (Fagundes et al 1996;Strauss et al 2009;Byk & Del-Claro 2010). Moreover, due to the plants reduce greatly the nectar secretion when this resource is removed in low frequency (Koptur 1983;Pyke 1991;Heil et al 2000), the ants' visitation on EFN of A. verrucosa may also have night foraging in arid and semi-arid regions (Briese & Macauley 1980;Oliveira et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In regions with high temperature and low humidity during the day (e.g. Neotropical savanna), most herbivores display strong nocturnal activity due to their ecophysiological limitations (Fagundes et al 1996;Strauss et al 2009;Byk & Del-Claro 2010). Therefore, a change in the nectar secretion during periods with high herbivory and/or high levels of water stress can reduce energy loss in 'superfluous' EFN secretion, and reduce the risk of EFN fungal infections (Heil et al 2000;Holland et al 2010;Yamawo et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that factors common to disturbed, but not necessarily urban, forests reduce seedling recruitment. For example, introduced species, which we observed at some urban and rural sites, are known to negatively impact native species through competition (Mack et al 2000) or herbivory (Nystrand and Granström 2000;Pigot and Leather 2008;Strauss et al 2009). Regardless of cause, the lack of regeneration is consistent with other observations of early life-history stage trees in urban areas (Broshot 2007;Lehvävirta and Rita 2002;Zipperer 2002).…”
Section: Urbanization Impacts On T Plicata Recruitment and Growthmentioning
confidence: 95%
“…Because generalist herbivores are widespread and present in both the native and nonnative ranges of invaders and apparently cannot be escaped, ecologists have focused almost exclusively on the release of invaders from specialists and the potential of reintroducing specialists to control invaders (Mu¨ller-Scha¨rer and Schaffner 2008). However, there are few if any generalist consumers of plants that do not have preferences, and the preferences of generalists can completely transform the composition and diversity of plant communities (Huntly 1990, Strauss et al 2009). Furthermore, recent studies have suggested that broad or single-family native generalists avoid some invasive plant species , Wikstro¨m et al 2006, Parker and Gilbert 2007, Han et al 2008, Jogesh et al 2008, Tallamy et al 2010; but see Lind and Parker 2010).…”
Section: Introductionmentioning
confidence: 99%